An Overview of Low-cost Housing Demand-Supply Gap in Malaysia: The Way Forward - Ebekoziena, Andrew; Abdul-Aziz, Abdul-Rashid; Jaafar, Mastura (School of Social Sciences, USM, 2017)
The purpose of this paper is to assess the low-cost housing (LCH) provision with a view to suggesting ways to abridge the demand-supply gap in Malaysian LCH. The Malaysian government over the years have attempted to make home ownership for all households regardless of the household income monthly but it seems this is becoming an illusion because of the increasing gap between the demand and supply of LCH provision. Therefore, this paper presents the preliminary findings of an on-going study that is examining the demand-supply gap in Malaysian LCH provision as well as role expected by the 5-year housing plan. It is little wonder that both the public and the private sector providers of LCH have not been able to meet up with the planned (demand) LCH as against what was achieved (supply) over a long period of time. Hence, this paper serves as a basis for further research into establishing the actual demandsupply gap of LCH provision in Malaysia. Compliance by all stakeholders to Malaysian 2011 National Housing Policy can no longer be over-emphasised and long overdue. Also, increasing the supply of LCH via tax incentives, government grants, government guarantees for house loans, and Bank Negara Malaysia’s mandate investment lenders to lend to target group among others were recommended to abridge the demand-supply gap of Malaysian LCH.